2001
DOI: 10.1074/jbc.m105675200
|View full text |Cite
|
Sign up to set email alerts
|

The Basic Helix-Loop-Helix Domain of the Aryl Hydrocarbon Receptor Nuclear Transporter (ARNT) Can Oligomerize and Bind E-box DNA Specifically

Abstract: The aryl hydrocarbon receptor nuclear transporter (ARNT) is a basic helix-loop-helix (bHLH) protein that contains a Per-Arnt-Sim (PAS) domain. ARNT heterodimerizes in vivo with other bHLH PAS proteins to regulate a number of cellular activities, but a physiological role for ARNT homodimers has not yet been established. Moreover, no rigorous studies have been done to characterize the biochemical properties of the bHLH domain of ARNT that would address this issue. To begin this characterization, we chemically sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
33
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 39 publications
(55 reference statements)
3
33
1
Order By: Relevance
“…This domain is found in over one-third of Arabidopsis bHLH TF family members (Supplemental Data Set 3). The bHLH transcription factors usually function in dimer or tetramer form or by forming a complex with other TF family members (Ellenberger et al, 1994;Ma et al, 1994;Huffman et al, 2001;Li, 2014;Chang et al, 2015); often the bHLH motif is required for dimerization. In this study, we demonstrated that the plantspecific BIF domain is also important for the dimerization and the normal function of DYT1.…”
Section: The Bif Domain Is Required For Dyt1 Functionmentioning
confidence: 99%
“…This domain is found in over one-third of Arabidopsis bHLH TF family members (Supplemental Data Set 3). The bHLH transcription factors usually function in dimer or tetramer form or by forming a complex with other TF family members (Ellenberger et al, 1994;Ma et al, 1994;Huffman et al, 2001;Li, 2014;Chang et al, 2015); often the bHLH motif is required for dimerization. In this study, we demonstrated that the plantspecific BIF domain is also important for the dimerization and the normal function of DYT1.…”
Section: The Bif Domain Is Required For Dyt1 Functionmentioning
confidence: 99%
“…Homodimerization of Arnt and Arnt H378P-Arnt can form a heterodimer with AhR and HIF1␣, but it also homodimerizes and binds E-box sequences (25,34,35). We investigated the ability of ArntH378P to homodimerize with either WT or mutant Arnt, using the mammalian two-hybrid assay with GAL4DBD-Arnt-bHLHPAS or GAL4DBD-ArntH378P-bHL-HPAS as bait (Fig.…”
Section: Physical Interaction and Transcriptional Activity Of Arnt Anmentioning
confidence: 99%
“…Complexes of the A13 DNA binding domain peptide and DNA were assessed for their oligomerization state using sedimentation equilibrium ultracentrifugation on a Beckman Coulter XL-1A Protein Analysis System as described (Huffman et al, 2001). A self-annealing fluorescein-labeled oligonucleotide, 5Ј-6-FAM-CCCATAAACCCCCCCGGTT-TATGGG-3Ј (5 M) was combined with the A13 DNA binding peptide (6 M to 10 M) in a buffer containing 80 mM KCl, 10 mM MgCl 2 , 0.2 mM EDTA, 1 mM dithiothreitol, and 20 mM Tris.HCl pH 7.8.…”
Section: Oligomerization Analysis Of the Hoxa13 Dna Binding Peptide Amentioning
confidence: 99%